Pelaksanaan Cluster Learning System di Masa Pandemi Covid-19 di Sekolah 3T - Sunarto Sunarto; Zulfikar Zulfikar (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the implementation of the Cluster Learning System during the Covid-19 pandemic in 3T schools. This research was conducted at SMP Negeri 7 Budong-budong, geographically this school is located in Mamuju Tengah District, West Sulawesi Province. Central Mamuju Regency is one of the underdeveloped districts in Indonesia. This study used a qualitative approach to describe the implementation of the Cluster Learning System during the Covid-19 pandemic in 3T schools. Data obtained through observation, interview, and documentation study techniques. Meanwhile, the data analysis process used data analysis techniques proposed by Miles and Hubermen which consisted of three activity lines, namely data reduction, data presentation, and conclusion drawing. From the research results, it was found that in implementing the Cluster Learning System there were 3 stages carried out by the SMP Negeri 7 Budong-budong, namely the planning, implementation, and evaluation stages. In addition, in the application of the Cluster Learning System at SMP Negeri 7 Budong, there are several advantages and disadvantages.